Are we undertreating calcium deficiency in metabolic bone disease of prematurity? A case report and review - Boddu, Sirisha Kusuma; Lankala, Reena (Frontiers in Pediatrics, 2022)
Background Both calcium (Ca) and phosphorus (P) are needed to prevent and treat metabolic bone disease (MBDP). However, the predominant focus of many treating neonatologists lies in supplementing P and vitamin D. In this report, we describe a VLBW infant with severe MBDP due to inadequately treated calcium deficiency and discuss the need to recognize this entity. Case details and management A 25-week, 700 gm baby boy had chronic lung disease and necrotizing enterocolitis. He received total parenteral nutrition, budesonide, furosemide, and caffeine. With high serum alkaline phosphatase (ALP: 1,700 IU/L) and low P (2.8 mg/dl), MBDP was diagnosed at 12 weeks, started on oral phosphate, human milk fortifier, and 1,400 IU/d of vitamin D before discharge. He was readmitted 2 weeks later with decreased lower limb mobility and respiratory distress. X-rays revealed severe osteopenia and fractures of both femurs. Serum P was 4.6 mg/dl but ALP was high (1,700 IU/L), and Ca was low (6.4 mg/dl). Parathyroid hormone (PTH: 605 pg/ml) and 25-hydroxy Vitamin D (25 OHD > 200 ng/ml) were very high. We discontinued his P and vitamin D, hypocalcemia treated with IV Ca gluconate, later oral Ca citrate, and calcitriol. Phosphate was added after normalization of Ca. Over the next many weeks, X-rays and biochemistry improved. Discussion MBDP results from both Ca and P deficiencies, especially in VLBW infants with comorbidities. P supplementation without treating underlying calcipenia can precipitate hypocalcemia and worsen osteopenia with disastrous consequences. In severe calcipenia, active vitamin D might have a role in addition to an appropriate dose of elemental calcium.